Semiotics of Organizational Culture:: Islamic Perspectives on Telkom Indonesia’s Instagram Reels Strategy - Fuad Adi Putra; Dina Hadi Lana; Yunita Sari (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The normalization of organizational ethics through short-form digital content has become a strategic issue in contemporary institutional communication, particularly as social media increasingly functions as a space for moral regulation and value transmission. This study examines the representation of organizational culture values in Instagram Reels content published by the @livingintelkom account, focusing on the “Do’s & Don’ts Telkomers Edition.” The research aims to analyze how visual and verbal signs construct meanings related to ethics, discipline, responsibility, and professionalism, and how these meanings operate within the framework of Islamic communication and digital da’wah. Using a qualitative descriptive-interpretative approach, this study employs Roland Barthes’ semiotic analysis to explore denotative, connotative, and ideological meanings embedded in the content. The findings indicate that Instagram Reels function not merely as informational or promotional media, but as symbolic instruments for internalizing organizational culture and shaping ethical work behavior. The values represented, such as integrity, discipline, accountability, and professionalism, are closely aligned with the principles of Islamic communication, particularly da’wah bil ḥāl, where moral messages are conveyed through exemplary practice rather than verbal instruction. Theoretically, this study contributes by integrating semiotics, organizational culture, and Islamic communication studies. Practically, it offers insights for organizations in designing value-based digital communication strategies that reinforce ethical behavior in the digital era.